Решение краевых задач теории пластин с переменными параметрами с применением периодических В-сплайнов - Григоренко, Я.М.; Крюков, Н.Н. (Прикладная механика, 2018)
В данной статье на примере решения задач об изгибе кольцевых пластин предложен подход, который базируется на использовании метода сплайн-коллокации, когда разрешающая система уравнений и краевые условия формулируются в перемещениях, усилиях и моментах, т.е. в смешанной форме. Запропоновано підхід до розв’язання задач статики кільцевих пластин зі змінними параметрами в двох координатних напрямках. Система рівнянь і крайові умови формулюються в переміщеннях і зусиллях – моментах. Підхід базується на зведенні двовимірної крайової задачі до одновимірної за допомогою методу сплайн-колокацій та розв’язання останньої стійким чисельним методом дискретної ортогоналізації. Числові результати наведено у вигляді таблиць та проаналізовано. An approach is proposed to solving the static problems of ring plates with variable parameters in two coordinate directions. The system of equations and boundary conditions are formulated in displacements and forces-moments. This approach is based on reduction of the two-dimensional problem to one-dimensional one by means of the spline collocations method and solving the last problem by a stable numerical method of discrete orthogonalization. The numerical results are given in tables and then analyzed.